Is the Medium Really the Message: Disambiguating the Sender’s Role. - Aganbi, Victor (IJRDO - Journal of Business Management, 2021)
McLuhan uses the term ’message’ to signify both the content of the medium as a message which can be easily grasped and the character of the medium as another message which can be easily overlooked. He proposed that it was the medium itself that shaped and controlled "the scale and form of human association and action", suggesting that the "content of any medium is always another medium.” Thus, speech is the content of writing, writing is the content of print, and print itself is the content of the telegraph. Does this mean that the medium is everything and everything is the medium? This Marshallian postulation leaves the role of the source/sender as the message creator as well as the medium and target audience selector in limbo. This article while agreeing with McLuhan that a medium is not something neutral as it takes hold of people and massages them, especially a new medium, notes nevertheless, that it’s all at the behest and pleasure of the source/sender. This study uses in-depth literature review, analyses and synthesis to resolve this research question in favour of the sender as the message himself, and all other elements of the communication process take life from him.